EvaluaciÃ³n TomogrÃ¡fica del Infarto Cerebral Agudo Mediante MensajerÃa InstantÃ¡nea (Revista de Medicina Clinica, 2018)
Introduction: A barrier to implementing intravenous thrombolysis in acute cerebral infarction is the lack of specialized personnel to evaluate the tomography of said patient. Objectives: The purpose of this work was to use instant messaging over the Internet as a telemedicine strategy, WhatsApp. Materials and Methods: The tomographies of patients with acute cerebral infarction were used, qualifying the ASPECTS scale by a panel of radiologists trained in qualifying said scale. The images were then photographed with a mobile phone and sent to 3 vascular neurologists by Whastapp, and they had to rate the ASPECTS scale on their mobile phones. The results obtained were compared between the panel, looking for Spearman correlation, as well as logistic regression for a dichotomized result variable in ASPECTS of 8 or more and 7 or less. Results: An excellent correlation was found between eachvascular neurologist and the panel of radiologists (Observer 1, 0.872, p = 0.27, Observer 2, 0.947, p = 0.007, Observer 3, 0.975, p = 0.002). When using the dichotomous result variable (7 and less, 8 and more) the correlation was 100% (1.0). Discussion: The evaluation of images of acute cerebral infarction and the qualification of the ASPECTS scale via instant messaging in mobile phones correlates very closely with the evaluation carried out in a conventional workstation. It is necessary to extend this study to ensure its applicability. Rev Med Clin 2018;2(1):8-12.
Keywords: Acute cerebral infarction; Stroke; Thrombolysis; Telemedicine; ASPECTS; TPa; Mobile telephony